2015
DOI: 10.1007/s11244-015-0421-x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of O−-Centers on Single Crystalline MgO(001)-Films

Abstract: Defects play an important role for understanding the properties of oxide surfaces. However, a detailed atomistic characterization of the properties of defects in particular of point defects is still a challenging task. On polycrystalline material it is the large variety of different species in terms of local environment, electronic properties as well as the metastable nature of most of these species, which complicates matters. EPR spectroscopy has proven to be a versatile tool to characterize electronic proper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 72 publications
0
3
0
Order By: Relevance
“… The underlying metal may contribute even more strongly if cations diffuse into the film and act as dopants. For example, MgO films grown on Mo(100) have been shown to contain Mo­(V) centers, which appear to be situated at the surface. , It seems likely that this would also influence the properties of adatoms on the MgO film, as Mo dopants in CaO(001) films, for example, have been shown to donate charge to adsorbed Au clusters, changing their shape …”
Section: Magnesium Oxide (Mgo)mentioning
confidence: 99%
“… The underlying metal may contribute even more strongly if cations diffuse into the film and act as dopants. For example, MgO films grown on Mo(100) have been shown to contain Mo­(V) centers, which appear to be situated at the surface. , It seems likely that this would also influence the properties of adatoms on the MgO film, as Mo dopants in CaO(001) films, for example, have been shown to donate charge to adsorbed Au clusters, changing their shape …”
Section: Magnesium Oxide (Mgo)mentioning
confidence: 99%
“…36,37 Electron paramagnetic resonance (EPR) shows that paramagnetic centers formed during the electron transfer process under molecular reaction conditions are preferably found at step edges and thicker MgO films. 38,39 However, the identification of non-paramagnetic centers at surface sites of oxide materials is less straightforward. 20 Density-functional theory (DFT) calculations have shown that surface chemical reactions can be controlled by defects located at the oxide-metal interface.…”
Section: Introductionmentioning
confidence: 99%
“…This result further corroborates the assignment of the observed species to trapped electron centers, as it shows that all three g-tensor components have to be quite similar. This excludes the presence of oxygenbased paramagnetic centers, which would have at least one g-tensor component shifted significantly to higher g values [22,[27][28][29][30][31]. Rotation of the magnetic field in the surface plane, as exemplified by a measurement with the magnetic field oriented along the [100] direction of the MgO lattice, results in the same resonance position.…”
mentioning
confidence: 99%